Study on Hydrochemical Evolution Mechanism of Groundwater in Coal Mine - Chai, Shuangwei (International Journal of Natural Resources and Environmental Studies, 2025)
In this paper, Pingdingshan coal mine is selected as the research area. Based on the conventional hydrochemical data of groundwater in coal mines, mathematical statistics and hydrogeochemical simulation are used to explore the evolution mechanism of groundwater hydrochemistry in the study area. It is indicated that the hydraulic connection of different water bodies is close, and there are many types of hydrochemical types, such as HCO3-Ca·Mg and HCO3-Na. The formation of each hydrochemical component is mainly controlled by water-rock interaction. Among them, Na++K+ mainly come from the dissolution process of salt rock, Ca2+, Mg2+ and HCO3- mainly come from the dissolution of carbonate rock, and SO42-mainly comes from the dissolution of gypsum.